1997
DOI: 10.1038/sj.onc.1201445
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of MCF7 human breast carcinoma cells to TNF-induced cell death is associated with loss of p53 function

Abstract: We have investigated the relationship between the development of tumor resistance towards the cytotoxic action of tumor necrosis factor-a (TNF) and p53 function, using the TNF-sensitive MCF7 human breast adenocarcinoma cell line and two TNF-resistant sublines, MCF7/R-A1 and MCF7/Adr. Use of single-strand conformation polymorphism (SSCP) analysis and DNA sequencing shows that MCF7 has a wild-type p53 gene, whereas both TNF-resistant sublines exhibit mutant p53. This includes a point mutation R280K in MCF7/R-A1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
1
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 40 publications
3
71
1
1
Order By: Relevance
“…In this context, we have previously shown that while MCF7 has a wt p53 gene, both TNF resistant sublines (1001 and MCF7/ADR) derived from the parental MCF7 cells exhibit mutant p53, resulting in loss of p53 transactivation functions. Furthermore, we have shown that impairment of wild-type p53 function may contribute to cell resistance towards the cytotoxic action of TNF and provided evidence that the disruption of wild-type p53 protein resulted in loss of the cytotoxic activity of TNF (Cai et al, 1997b). It should be noted that MCF7 cells are caspase 3 de®cient (Janicke et al, 1998 and our unpublished results).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In this context, we have previously shown that while MCF7 has a wt p53 gene, both TNF resistant sublines (1001 and MCF7/ADR) derived from the parental MCF7 cells exhibit mutant p53, resulting in loss of p53 transactivation functions. Furthermore, we have shown that impairment of wild-type p53 function may contribute to cell resistance towards the cytotoxic action of TNF and provided evidence that the disruption of wild-type p53 protein resulted in loss of the cytotoxic activity of TNF (Cai et al, 1997b). It should be noted that MCF7 cells are caspase 3 de®cient (Janicke et al, 1998 and our unpublished results).…”
Section: Discussionsupporting
confidence: 53%
“…For this purpose, we used TNF-sensitive breast adenocarcinoma MCF7 cells and TNF-resistant derivatives 1001 clone and MCF7/ADR cells ( Figure 1a). In a previous study, we have demonstrated a correlation between cell resistance to the cytotoxic action of TNF and p53 function (Cai et al, 1997b). Using SSCP (single-strand conformation polymorphism) analysis and DNA sequencing, we have shown that while MCF7 has a wt p53 gene, both TNF resistant sublines (1001 and MCF7/Adr) derived from the parental MCF7 cells exhibit mutant p53.…”
Section: Functional Wt P53 Expression Following Adwtp53 Infection Of mentioning
confidence: 92%
See 2 more Smart Citations
“…Recently, we have shown that the resistance of human breast adenocarcinoma cell line MCF7 to the cytotoxic action of TNF was associated with the loss of p53 function. 30 Moreover, we have demonstrated that the transfer of wtp53 using an adenoviral vector ( Adwtp53) reestablishes TNF sensitivity in TNF -resistant cells. 31 In the present study, we investigated the mechanisms of the p53 -mediated restoration of TNF sensitivity.…”
mentioning
confidence: 99%